SOCIAL CONFLICTS FOUND IN THE LEGENDS OF DAYANG MERINDU AND NAYA SENTIKA AND THEIR IMPLEMENTATIONS IN LITERATURE LEARNING - Eka Putri; Mulyadi Eko Purnomo; Santi Oktarina (University of Kuningan, 2023)
This research describes the realizations of social conflicts, the function of social conflict, the similarities and differences of Dayang Merindu and Naya Sentika legends, and the implications on literature learning. The research applied a descriptive comparative method supported by an objective approach. Then, the researchers analyzed the data by collecting, reducing, presenting, and concluding the data. The data sources were the legends of Dayang Merindu and Naya Sentika. The research data were social conflict realizations and functions of the legends in the form of text excerpts. The results showed differences in the legends. The legend of Dayang Merindu had three types of conflicts: interpersonal, interest, and inter-social conflicts. The legend of Naya Sentika had four types of conflicts: interpersonal, interest, inter-group, and international conflicts. The similarities of the legends were the social functions of the conflicts. They were two functions: solidarity and communicative functions. The current research results are applicable for literature learning and further reading sources as the realization of literature appreciation.